Comparative Analytical Study on Crack Width of Reinforced Concrete Structures - Ahmed A. Abu El Naas; Hany M. El Hashimy; Khaled F. El Kashif (Salehan Institute of Higher Education, 2021)
This paper presents a comparative study for the cracking limit state according to design codes. It aims mainly to connect research findings with design code equations. Appropriate recommendations are reached and the various factors and parameters influencing crack width investigated. The most appropriate equation for crack width calculation can be found. This is done by creating an analytical and numerical program studied various factors and parameters affecting on the crack width. The Analytical study includes some variables affecting the crack width such as steel stress, concrete cover, flexural reinforcement ratio and rebar arrangement. A 3-D finite element analysis by ABAQUS were used to model and idealize the problem. The numerical results were compared with the analytical results. It was concluded that some codes did not take into account the impact of some major variables and cases on the crack width. Also, it was found that some codes are not clear in the region concerning the position of the crack width calculation and the values obtained for the crack width. For calculating crack width values, JSCE (2007) equation is the most appropriate equation as it takes into account the main parameters that affect crack width. Doi: 10.28991/cej-2021-03091720 Full Text: PDF